The case of the speluncean explorers : nine new opinions - Suber, Peter (Routledge, 1998)
Lon L. Fuller published his "The Case of the Speluncean Explorers" in 1949 (Harvard Law Review, vol. 62, no. 4), an invented legal case with opinions by "supreme court judges" meant to reflect differing legal philosophies. It is reprinted here, with nine new opinions by Peter Suber.